Alih Kode dalam Komunikasi Lisan antara Dosen dan Mahasiswa di STAIN Jember: Code-Switching in Oral Communication between Lecturers and Students at the State Islamic College (STAIN) Jember - St. Mislikhah (Fenomena, 2006)
In bilingual or multilingual academic settings, code-switching is a natural yet often overlooked phenomenon that shapes classroom and informal communication between lecturers and students. Grounded in the sociolinguistic framework of code-switching, this study addresses the gap in understanding its patterns, causes, and purposes within Indonesian higher education. The research aims to describe code-switching patterns, identify the factors that influence them, and explain the communicative goals behind code-switching in oral interactions at STAIN Jember. A descriptive qualitative approach was employed, involving observations, interviews, and documentation of ten speech events between lecturers and students, both inside and outside the classroom. The findings reveal that code-switching occurs in the forms of language switching (Javanese-Indonesian and Madurese-Indonesian) and variety switching (formal to informal, complete to concise). The main factors include the speaker, interlocutor, and topic of discussion. The study concludes that code-switching serves six key purposes: emphasizing material, generating humor, building rapport, expressing surprise, showing annoyance, and demonstrating respect. Recommendations include integrating code-switching awareness into lecturer training and communication curricula. Dalam lingkungan akademik bilingual atau multilingual, alih kode merupakan fenomena alami namun sering diabaikan yang membentuk komunikasi lisan antara dosen dan mahasiswa. Penelitian ini berlandaskan kerangka sosiolinguistik tentang alih kode dan bertujuan mendeskripsikan pola, faktor penyebab, serta tujuan alih kode dalam komunikasi lisan di STAIN Jember. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik observasi, wawancara, dan dokumentasi pada sepuluh peristiwa tutur antara dosen dan mahasiswa. Hasil penelitian menunjukkan bahwa alih kode terjadi dalam wujud alih bahasa (Jawa-Indonesia dan Madura-Indonesia) serta alih ragam (formal ke nonformal, lengkap ke ringkas). Faktor penyebabnya meliputi pembicara, mitra bicara, dan topik pembicaraan. Penelitian menyimpulkan bahwa alih kode memiliki enam tujuan utama: memberikan penegasan materi, membangkitkan humor, membina keakraban, mengungkapkan keterkejutan, menunjukkan kejengkelan, dan mengekspresikan rasa hormat. Rekomendasi penelitian ini adalah perlunya peningkatan kesadaran tentang alih kode dalam pelatihan dosen dan kurikulum komunikasi.